1995
DOI: 10.1111/j.1365-2621.1995.tb06207.x
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Reduction in Liquid Egg Yolk using β‐Cyclodextrin

Abstract: A process to reduce cholesterol in liquid egg yolk using P-cyclodextrin (CD) was optimized by response surface methodology, based on cholesterol reduction and yield. The most important factors influencing cholesterol reduction were dilution of egg yolk to a defined water:solid ratio and CD concentration. In the final process, egg yolk was adjusted to pH 10.5, diluted to a water:solid ratio of 2.9, heated to 5O"C, and CD added at a CD:cholesterol molar ratio of 4.0. The slurry was mixed for 6.5 min at 1800 rpm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 12 publications
1
20
0
Order By: Relevance
“…There was no significant difference with further addition of β-CD. Smith et al [28] reported that protein reduction of 9.2 % with 89.2 % cholesterol reduction in liquid egg yolk using β-CD which proven better reduction of cholesterol with 98% reduction of cholesterol with almost less than 9 % protein reduction in this study.…”
Section: Protein Quantificationsupporting
confidence: 58%
“…There was no significant difference with further addition of β-CD. Smith et al [28] reported that protein reduction of 9.2 % with 89.2 % cholesterol reduction in liquid egg yolk using β-CD which proven better reduction of cholesterol with 98% reduction of cholesterol with almost less than 9 % protein reduction in this study.…”
Section: Protein Quantificationsupporting
confidence: 58%
“…β-CD had the advantages of non-toxicity (Rao et al 2000), nonhygroscopic and chemical stability (Nagatomo 1985). It was widely used for removing cholesterol from lard (Yen and Tsui 1995), cream (Ahn and Kwak 1999) and egg yolk or whole egg (Ravichandran and Divakar 1998;Smith et al 1995). But commercial β-CD was expensive and its wastage during the process also led to environmental problems.…”
Section: Introductionmentioning
confidence: 99%
“…Cyclodextrins have been used as encapsulating agents for various purposes such as stabilisation of aroma, docosahexaenoic acid (DHA) and vitamins (Bhandari, D'Arcy, & Padukka, 1999;Goubet et al, 2001;Hashimoto, 2006), taste modification (Szejtli & Szente, 2005) and cholesterol removal (Smith, Awad, Bennink, & Gill, 1995).…”
Section: Introductionmentioning
confidence: 99%